2020
DOI: 10.1161/circresaha.120.317086
|View full text |Cite
|
Sign up to set email alerts
|

Large Extracellular Vesicle-Associated Rap1 Accumulates in Atherosclerotic Plaques, Correlates With Vascular Risks and Is Involved in Atherosclerosis

Abstract: Rationale: Metabolic syndrome (MetS) is a cluster of interrelated risk factors for cardiovascular diseases and atherosclerosis. Circulating levels of large extracellular vesicles (lEVs), submicrometer-sized vesicles released from plasma membrane, from MetS patients were shown to induce endothelial dysfunction but their role in early stage of atherosclerosis and on vascular smooth muscle cells (SMC) remain to be fully elucidated. Objective: To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…Platelet-derived EVs can induce SMC proliferation and migration by inducing a proinflammatory phenotype in SMCs [ 162 , 163 ]. Proteomic analysis of EVs, revealed that Ras-related protein 1 (Rap1) was overexpressed in patients with metabolic syndrome compared to healthy donors [ 164 ]. A larger proportion of Rap1 + EVs originating from platelets, promoted SMC migration and proliferation probably via ERK5 activation in vitro and these effects were abolished after Rap1 inhibition [ 164 ].…”
Section: Ev Signalling In Atherosclerosis Progressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Platelet-derived EVs can induce SMC proliferation and migration by inducing a proinflammatory phenotype in SMCs [ 162 , 163 ]. Proteomic analysis of EVs, revealed that Ras-related protein 1 (Rap1) was overexpressed in patients with metabolic syndrome compared to healthy donors [ 164 ]. A larger proportion of Rap1 + EVs originating from platelets, promoted SMC migration and proliferation probably via ERK5 activation in vitro and these effects were abolished after Rap1 inhibition [ 164 ].…”
Section: Ev Signalling In Atherosclerosis Progressionmentioning
confidence: 99%
“…Proteomic analysis of EVs, revealed that Ras-related protein 1 (Rap1) was overexpressed in patients with metabolic syndrome compared to healthy donors [ 164 ]. A larger proportion of Rap1 + EVs originating from platelets, promoted SMC migration and proliferation probably via ERK5 activation in vitro and these effects were abolished after Rap1 inhibition [ 164 ]. Elevated levels of Rap1 were detected on circulating EVs from high fat fed apoE −/− mice too [ 164 ].…”
Section: Ev Signalling In Atherosclerosis Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atherosclerosis is one of the main causes of cardiovascular death in developed countries [17]. More and more evidence shows that oxidative stress plays a key role in the formation of atherosclerosis [44,45]. The activation of proinflammatory signal pathway, the expression of cytokines/chemokines, and the increase of oxidative stress are some of the mechanisms underlying atherosclerosis [20].…”
Section: Atherosclerosismentioning
confidence: 99%